Metabolic changes during carbon monoxide poisoning: An experimental study. Issue 11 (5th May 2021) - Simonsen, Carsten; Magnusdottir, Sigriður Olga; Andreasen, Jan Jesper; Wimmer, Reinhard; Rasmussen, Bodil Steen; Kjærgaard, Benedict; Maltesen, Raluca Georgiana
Abstract: Carbon monoxide (CO) is the leading cause of death by poisoning worldwide. The aim was to explore the effects of mild and severe poisoning on blood gas parameters and metabolites. Eleven pigs were exposed to CO intoxication and had blood collected before and during poisoning. Mild CO poisoning (carboxyhaemoglobin, COHb 35.2 ± 7.9%) was achieved at 32 ± 13 minutes, and severe poisoning (69.3 ± 10.2% COHb) at 64 ± 23 minutes from baseline (2.9 ± 0.5% COHb). Blood gas parameters and metabolites were measured on a blood gas analyser and nuclear magnetic resonance spectrometer, respectively. Unsupervised principal component, analysis of variance and Pearson's correlation tests were applied. A P ‐value ≤ .05 was considered statistically significant. Mild poisoning resulted in a 28.4% drop in oxyhaemoglobin (OHb) and 12‐fold increase in COHb, while severe poisoning in a 65% drop in OHb and 24‐fold increase in COHb. Among others, metabolites implicated in regulation of metabolic acidosis (lactate, P  < .0001), energy balance (pyruvate, P  < .0001; 3‐hydroxybutyrc acid, P  = .01), respiration (citrate, P  = .007; succinate, P  = .0003; fumarate, P  < .0001), lipid metabolism (glycerol, P  = .002; choline, P  = .0002) and antioxidant‐oxidant balance (glutathione, P  = .03; hypoxanthine, P  < .0001) were altered, especially during severe poisoning. Our study adds new insights into the deranged metabolism of CO poisoning and leads the way for further investigation.